(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2022)
This article explores the affinities between animation practice and experiments in perception by Gestalt psychologists. By drawing out a Gestalt style of seeing — a sensitivity to the visual forces that scaffold an image — we can better describe movements, figures, and spaces in animation. Although these affinities make Gestalt appropriate for discussing animation, they do not necessarily imply that animated films merely illustrate or independently verify Gestalt laws of perception. Rather, they suggest two branches of cultural practice sharing what philosopher of science Ian Hacking calls a ‘style of reasoning’: a regularized procedure whose consistent results form a basis for knowledge in a given culture. This article argues that Gestalt and animation are co-participants in the ‘culture of design’: a project of shaping sensory arrangements in order to shape populations, which began in the nineteenth century and has gained force through the present day. It is this culture of design, which includes the exploration of cinema as an art of graphic arrangement, that has become all-but-ubiquitous in the 21stcentury and has led to the ubiquity of animation.